1998
DOI: 10.1523/jneurosci.18-18-07543.1998
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent pH Shifts and Periodic Recurrence of Spontaneous Interictal Spikes in a Model of Focal Epileptogenesis

Abstract: The mechanisms that control the periodicity of spontaneous epileptiform cortical potentials were investigated in the in vitro isolated guinea pig brain preparation. A brief intracortical application of bicuculline in the piriform cortex induced spontaneous interictal spikes (sISs) that recurred with high periodicity (8.5 Ϯ 3.1 sec, mean Ϯ SD). Intracellular recordings from principal neurons showed that the early phase of the inter-sIS period is caused by a GABAb receptor-mediated inhibitory potential. The late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 142 publications
(100 citation statements)
references
References 55 publications
(86 reference statements)
2
98
0
Order By: Relevance
“…In a 4-AP model of epilepsy, carbenoxolone suppresses spontaneous large inhibitory postsynaptic currents and ectopic spikes [101] , and reduces the frequency and cumulative duration of spontaneous ictal-like activity, while the Cx36-selective blocker quinidine diminishes this activity [102] . Carbenoxolone [80,81] , octanol and 18α-glycyrrhetinic acid [103] also depress the spontaneous epileptiform discharges induced by bicuculline. In a Co 2+ epilepsy model, Mylvaganam et al demonstrated that octanol diminishes ictal and interictal discharges [79] .…”
Section: +mentioning
confidence: 97%
“…In a 4-AP model of epilepsy, carbenoxolone suppresses spontaneous large inhibitory postsynaptic currents and ectopic spikes [101] , and reduces the frequency and cumulative duration of spontaneous ictal-like activity, while the Cx36-selective blocker quinidine diminishes this activity [102] . Carbenoxolone [80,81] , octanol and 18α-glycyrrhetinic acid [103] also depress the spontaneous epileptiform discharges induced by bicuculline. In a Co 2+ epilepsy model, Mylvaganam et al demonstrated that octanol diminishes ictal and interictal discharges [79] .…”
Section: +mentioning
confidence: 97%
“…Several studies have addressed the question of how neuronal activity elicits changes in intracellular and extracellular H + concentration, sometimes yielding contrasting results (Caldwell et al, 2013;Chen and Chesler, 2015;Cichy et al, 2015;de Curtis et al, 1998;DeVries, 2001;Lu et al, 2012;Palmer et al, 2003;Zhang et al, 2010;Zhao et al, 2011). We studied the effects of sustained heightened neural activity on the extracellular H + concentration by using in vitro models of epileptic-like network states characterized by synchronized neuronal discharges.…”
Section: Neuronal Hyperactivity Causes Localized Extracellular Acidicmentioning
confidence: 99%
“…Seizure activity is of course defined by sustained synchronous discharge and has been shown to give rise to large summated alkaline shifts on the order of 0.10 -0.20 unit pH (de Curtis et al 1998). Synchronous discharge, however, is also a fundamental property of normal brain function.…”
Section: Fig 5 Kinetic Model Of Passive Bufferingmentioning
confidence: 99%